جهود خديجة الحديثي في دراسة كتاب سيبويه - حواس عربية; مدخل كوثر (University of El-oued, 2025)
سلط هذا البحث الضوء على جهود عالمة من أعلام النحو واللغة العربية، في دراسة وتوضيح كتاب سيبويه، وهي خديجة الحديثي التي قضت حياتها في العلم والتعليم، والتأليف والبحوث اللغوية والنحوية التي منها كتاب" الشاهد وأصول النحو في كتاب سيبويه" الذي يعد مصدرا أساسيا لأي باحث عربي في قواعد اللغة والصرف، ولهذا استحقت الدراسة لفهم وجهة نظرها اللغوية تجاه الكتاب. يتألف البحث من فصلين، مقدمة وخاتمة لتبين جهودها في هذا الكتاب، تناول الفصل الأول حياة خديجة الحديثي، وحياة سيبويه ولمحة عن الكتاب، فكان القسم الأول الشاهد في كتاب سيبويه، والقسم الثاني أصول النحو في كتاب سيبويه. ومن النتائج التي توصلت لها هذه الدراسة، أن خديجة الحديثي أول سيدة دخلت هذا المجال اللغوي، وأن لها جهود علمية باهرة، ومدى اهتمامها بكتاب سيبويه أنها اتبعت المنهج البصري النحوي، ولها آراء مهمة في مختلف فروع النحو، وخدمة اللغة العربية This research sheds light on the efforts of one of the prominent scholars in Arabic grammar and linguistics, Khadija Al-Hadithi, who dedicated her life to knowledge, teaching, authorship, and linguistic and grammatical research. Among her works is the book "Al-Shahid wa Usul al-Nahw fi Kitab Sibawayh" (The Evidence and the Principles of Grammar in Sibawayh's Book), which is considered an essential source for any Arab researcher in grammar and morphology. For this reason, this study seeks to understand her linguistic perspective toward the book. The research consists of two chapters, along with an introduction and a conclusion that present her efforts in this book. The first chapter addresses the life of Khadija Al-Hadithi, the life of Sibawayh, and an overview of his book. This chapter is divided into two sections: the first discusses the role of evidence in Sibawayh's Book, and the second explores the principles of grammar in Sibawayh's Book. Among the findings of this study is that Khadija Al-Hadithi was the first woman to enter this field of linguistics, and that she made outstanding scholarly contributions. The study also shows the extent of her interest in Sibawayh's Book, her adherence to the Basran grammatical methodology, and her significant opinions across various branches of grammar and her service to the Arabic language.
كتاب الشاهد وأصوله النحو في كتاب سيبويه انموذجا
مذكرة .ماستر . لسانيات عامة. 2025